(untitled) (Global Journal of Science Frontier Research, 2020)
One of the first electrostatic generators is Calvin’s dropper, which invented the lord Calvin in 1863. This generator gave the possibility to obtain voltage of up to 20 kV. Further development of electrostatic generators was the invention of the electric generator, developed between 1880 -1883 the British inventor By James by Whimshurst. This generator gave the possibility to obtain voltage of up to 100 kV and it is above. Wide practical use in the accelerating technology obtained de Graaf’s generator. This is the generator of the high voltage, the operating principle of which is based on the electrization of that moving dielectric tape. Such generator was developed American by the physicist By Robert van de Graaf in 1929 for year it made possible to obtain the voltage to 80 kV. In 1931 -1933 they built the more powerful generators, which made it possible to reach voltage in 1 MV and 7 MV respectively. In the article are described three new constructions of the electrostatic generators, one of which is pulse.